Kuliner Ndeso Blitar Kuto Cilik Sing Kawentar - SEKAR AGENG CAKRAWARTI SEKAR AGENG CAKRAWARTI; Resdianto Permata Raharjo (Program Studi Tata Boga Universitas Negeri Jakarta, 2022)
Abstract Blitar is the little kuto of Sing Kawentar. Blitar also has many tourist destinations that are able to provide a new atmosphere and learn how the heroes who used to fight for the Indonesian nation to the point of independence can be felt by the Indonesian people. This is what makes Blitar City educational tourism famous to foreign countries. Blitar City also has culinary delights that contain quite a lot of cholesterol. However, this food is one of the favorite foods of all Blitar people, especially for the people of Blitar Regency. This food is called blendrang tewel or commonly called young jackfruit vegetables that have been heated many times. When viewed from a health point of view, blendrang is an unhealthy food because the process of heating the food gradually removes some of the nutrients in the main ingredients used as the basic ingredients for making the don't fussy. even if we eat foods that pay attention to the nutrients and nutrients listed on these foods. not just good food. Instead, you must still consider foods that can be enjoyed because they taste good and the food you eat has a delicious and nutritious taste. This is the choice of a healthy way of life. If we choose delicious and nutritious food, our bodies can absorb these nutrients properly and correctly. Nutrients in these foods are very dependent on the process of accelerating metabolism. If you consume the right food and according to the portion or daily calorie needs, the body will receive and digest it easily and can absorb nutrients in the body optimally. This absorption will later become fat reserves which will then be used as a source of energy in the form of activities one day ahead. Keywords: culinary, traditional, little kuto of Sing Kawentar